Relative Tax Rates, Proximity, and Cigarette Tax Noncompliance: Evidence from a National Sample of Littered Cigarette Packs. (March 2019) - Wang, Shu; Merriman, David; Chaloupka, Frank
We analyze data about cigarette tax compliance from the first US-based national scale littered cigarette packs collection. We code each pack based on whether an appropriate tax had been paid at the location where it was found. Noncompliance across our 132 sample communities ranges from 0 percent to 100 percent with an appropriately weighted mean of 21 percent. We provide evidence that noncompliance is due to both cross-border shopping and cigarette trafficking. Ordinary least squares and binomial logit regressions demonstrate that the financial incentive for noncompliance is the most important explanatory variable and has a statistically and quantitatively significant impact on noncompliance. We find mixed evidence about the extent to which tax avoidance varies with distance to lower-tax borders. Our simulations show that, even after accounting for increased noncompliance, virtually all areas in our study would experience increases in tax revenue if they increased cigarette tax rates.